2016
DOI: 10.1007/s10620-016-4275-2
|View full text |Cite
|
Sign up to set email alerts
|

Many Inflammatory Bowel Disease Patients Are Not Immune to Measles or Pertussis

Abstract: A significant number of our IBD patients lack immunity to measles, and a majority of our IBD patients do not have detectable immunity to pertussis. Importantly, the majority of the measles non-immune patients are on ISS therapy and therefore unable to receive a booster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Over the last 10 years there has been an increase in the number of cases of measles in the United States, in part related to parents who intentionally have not vaccinated their children ( 19 ). A list of inactivated and live vaccines to consider are listed in Tables 2 and 3 .…”
Section: Vaccinationsmentioning
confidence: 99%
“…Over the last 10 years there has been an increase in the number of cases of measles in the United States, in part related to parents who intentionally have not vaccinated their children ( 19 ). A list of inactivated and live vaccines to consider are listed in Tables 2 and 3 .…”
Section: Vaccinationsmentioning
confidence: 99%
“…Cleveland et al , in a prospective study, showed that a significant number of IBD patients lack immunity to measles [69]. The MMR vaccine is only available as a live, attenuated vaccine.…”
Section: Vaccination Rate In Ibd Patientsmentioning
confidence: 99%
“…15 It is generally accepted that a single inactivated influenza vaccine has a sufficient effect in healthy adults and that no further increase in immunogenicity due to booster vaccinations occurs. 16, 17 The booster effect of the trivalent influenza vaccine in patients with IBD receiving immunosuppressive therapy has also been investigated, and although single vaccination was shown to be effective, 18 research on immunogenicity by treatment status is insufficient.…”
Section: Introductionmentioning
confidence: 99%